Short Time Preservation of Poultry Viscera Meal and its Potentiality as a Source of Protein in Broiler Diet - Redoy , Md. Rahat Ahmad; Rahman, Md. Mahbubur; Al-Mamun, Mohammad; Shaiful Islam, Khan Md. (International Journal of Poultry Science, 2021)
Background and Objective: Poultry viscera meal (PVM) is a by-product of poultry slaughterhouses having high protein value at a relatively lower price. However, in developing countries it is a big challenge to maintain the keeping quality of viscera from collection to processing due to small scale availability per day in open market. So, this experiment was designed to find suitable methods for short-term preservation of PVM before processing and recycling it as broiler feed. Materials and Methods: Fresh chicken viscera were collected from local market and preserved for 48 h, without preservative at (I) Room temperature (Normal sample), (ii) Chilling temperature (Chilled sample) and with (iii) 0.5% citric acid, (iv) 1.0% citric acid, (v) 0.5% sulfuric acid and (vi) 1.0% sulfuric acid at room temperature which collectively considered as preservative samples. Based on the findings, 1.0% citric acid treated PVM was selected for efficacy study in broiler. Experimental diets contained 0% PVM, 2.5% PVM and 5.0% PVM by replacing similar amount of protein concentrate. Results: The lowest free fatty acid and peroxide value was observed at the addition of 1.0% citric acid, whereas pepsin digestibility and microbial load were similar to 1.0% sulfuric acid but lower than others. In the feeding trial, the highest body weight gain was found at 0% PVM but the lowest feed cost was observed at 5.0% PVM. Conclusion: Overall, 1.0% citric/sulfuric acid could be added in poultry viscera for short-term preservation and PVM could be included in broiler diet up to 5.0% for cost-effective broiler production.